Assessing the service quality at health service facilities during the COVID-19 pandemic in North Buton District, Indonesia - La Ode Ali Imran Ahmad; Muhammad Ikhsan Akbar; Nurmaladewi Nurmaladewi; Pitrah Aspian; Iriyanto Pagala; Muhammad Rustam (Public Health of Indonesia, 2022)
Background: The degree of quality health is greatly influenced by existing health services. Thus, assessing the service quality during the COVID-19 pandemic is necessary.